2020
DOI: 10.3390/coatings10030256
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Deposition of Hyaluronan and Quercetin-Loaded Chitosan Nanoparticles onto Titanium for Improving Blood Compatibility

Abstract: Surface modification is an effective way to improve the hemocompatibility of biomaterials. Quercetin has significant anticoagulation and antithrombotic effects, and thus it is a promising candidate agent for the surface modification of blood-contacting materials. In this study, quercetin was successfully encapsulated in tripolyphosphate–chitosan nanoparticles (TCs) based on the ionic gelation of chitosan with tripolyphosphate (TPP) anions. Then, hyaluronan acid (HA)/quercetin-loaded TPP–chitosan nanoparticle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…CS NPs have been used for loading insulin and also applied in diabetes therapy [ 28 ]. Moreover, several food bioactive ingredients have been encapsulated in CS NPs, including curcumin [ 29 ], flavonoids [ 30 ], lutein [ 31 ], polyphenols [ 32 ], resveratrol [ 33 ], and vitamins (B9, B12, and C) [ 34 ]. Fish oils are rich in ω-3 PUFAs, which are highly prone to oxidation due to their higher content of unsaturated fatty acid undergoing lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…CS NPs have been used for loading insulin and also applied in diabetes therapy [ 28 ]. Moreover, several food bioactive ingredients have been encapsulated in CS NPs, including curcumin [ 29 ], flavonoids [ 30 ], lutein [ 31 ], polyphenols [ 32 ], resveratrol [ 33 ], and vitamins (B9, B12, and C) [ 34 ]. Fish oils are rich in ω-3 PUFAs, which are highly prone to oxidation due to their higher content of unsaturated fatty acid undergoing lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Although great progress has been made in the surface functionalization of titanium-based biomaterials, there are still many issues to be solved, including the delayed surface endothelialization, thrombosis, and infection after implantation [ 12 , 13 ]. Studies have shown that the surface properties of the implant are related not only to the surface bioactivities but also to the surface topographies.…”
Section: Introductionmentioning
confidence: 99%
“…This detection limit was expressed by Hemo-R. Hemo-R should not be more than 5%, indicating that the material could meet the biomedical requirements. 51,52 In this study, the direct method was that various proportions of the microfiber scaffold and collected fresh rabbit blood were co-incubated for 3 h, while distilled water and saline solution were used as positive and negative controls, respectively. As previous research had proven that pure SF has excellent blood compatibility, we did not test the pure SF experimental group.…”
Section: Resultsmentioning
confidence: 99%